Recurrences after stereotactic arrhythmia radioablation for refractory ventricular tachycardia. (19th May 2022) - Herrera Siklody, C; Schiappacasse, L; Jumeau, R; Le Bloa, M; Ozsahin, M; Teres Castillo, C; Moeckli, R; Porretta, AP; Pascale, P; Domenichini, G; Bourhis, J; Pruvot, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Stereotactic arrhythmia radioablation (STAR) has been recently introduced for the management of ventricular tachycardia (VT) refractory to antiarrhythmic drugs and catheter ablation (CA). VT recurrences have been reported after STAR but the mechanisms remain poorly known. We analyzed recurrences in our patients (pts) after STAR for refractory VT. Methods: From 09.2017 to 01.2020, 12 pts (66±8y, LVEF 40±14%) suffering from refractory VT were enrolled. The underlying cardiopathy was ischemic in 3, inflammatory in 3 and idiopathic in 6 pts. Nine out of 12 pts had a history of at least 1 electrical storm. Before STAR, an invasive electro-anatomical mapping of the VT substrate (VT-sub) was performed. A mean dose of 22±2Gy was delivered to the VT-sub using the Cyberknife system. Results: The ablation volume was 24±7cc and involved the basal interventricular septum (IVS) in 10 pts. During the first 6 months after STAR, VT burden decreased by 95% (mean value, from 930 to 46 VT/semester). After a median follow-up of 14±10 months, 10/12 (83%) developed a recurrence as a sustained VT and underwent a redo CA. VT recurrence was located at the border zone (BZ) of the treated VT-sub in 6 cases, involved both the BZ and a larger substrate in 2 cases, and occurred remote from the VT-sub in 2 cases (see Table). The dose delivered at sites of VT recurrence was 9.9±8.6 Gy with a large heterogeneity ranging from 0.11 to 28.37 Gy, for some patients due to dose constraints near critical structures. Importantly no pts developed an AV block after STAR. Conclusion: STAR appears to be an efficient tool for the management of IVS refractory VT, leading to a strong VT burden reduction and no AV block. Recurrences were nevertheless common, often at the border zone of the irradiated volume.